2017
DOI: 10.3892/mmr.2017.7273
|View full text |Cite|
|
Sign up to set email alerts
|

MicroRNA-643 regulates the expression of ZEB1 and inhibits tumorigenesis in osteosarcoma

Abstract: Osteosarcoma is among the most malignant types of tumor worldwide and has become a leading contributor to tumor incidence, particularly in adolescents. Resistance to conventional treatment and the complexity of osteosarcoma tumorigenesis has resulted in high mortality rates. MicroRNAs are a class of noncoding RNAs, which regulate numerous biological processes. However, the involvement of miR-643 in osteosarcoma remains to be elucidated. In the present study, reverse transcription-quantitative polymerase chain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 30 publications
(31 reference statements)
0
19
0
Order By: Relevance
“…Zeb1 was shown to promote the progression of lung cancer by increasing the expression of MMP2, a member of the matrix metalloproteinases family that play an important role in cell migration and facilitate invasion and metastasis of tumor cells [18,19]. Zeb1 has also been shown to be upregulated in osteosarcoma, and to contribute to its development [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…Zeb1 was shown to promote the progression of lung cancer by increasing the expression of MMP2, a member of the matrix metalloproteinases family that play an important role in cell migration and facilitate invasion and metastasis of tumor cells [18,19]. Zeb1 has also been shown to be upregulated in osteosarcoma, and to contribute to its development [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…As we know, the function of miRNA is realized by regulating target expression in cancers and diseases. Previous studies have indicated many targets of miR‐643, including X‐linked inhibitor of apoptosis protein and zinc finger E‐box binding homeobox transcription factor 1 (Wang et al, 2017; Lopez‐Rosas et al, 2018). In this study, we first demonstrated TRAF6 as a target of miR‐643, which was confirmed by luciferase reporter assay and RIP.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, miR‐27a‐3p and miR‐124‐3p are also involved in endometritis development (Di Pietro et al, 2018). The increasing evidence disclose that miR‐643 is expressed and associated with the progression of multiple cancers or diseases, such as non‐small‐cell lung carcinoma, pancreatic cancer, osteosarcoma, and colon parasites infection (Sun et al, 2013; Shen et al, 2015; Wang et al, 2017; Lopez‐Rosas et al, 2018). More importantly, a previous study shows that 23 miRNAs were abnormally expressed in endometritis, in which miR‐643 expression is decreased the most but miR‐215 (Hailemariam et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Previously, it was reported that miR-643 functions as a tumor suppressor gene in osteosarcoma cells. It was showed that miR-643 suppressed the cancer hallmarks and as a bona fide tumor suppressor it may also activates apoptosis (Wang et al, 2017). XIAP has a central regulatory role in programmed cell death by inhibiting the caspases cascade (Deveraux and Reed, 1999).…”
Section: Discussionmentioning
confidence: 99%